A família e os efeitos da guarda parental na relação e apoio familiar dos adolescentes - Camacho, Inês (2019)
This study aimed to study social support among family members, and the effects of parental custody in communication with parents and in the family relationship. A total of 8125 Portuguese adolescents participated in the study, with 52,7% being female, attending the 6th, 8th, 10th and 12th grade in Portugal, as part of the Health Behaviour in School aged Children (HBSC) . The young people were asked if their parents lived in the same house, and if they did not live how was the parental guard. They were also questioned about the level of life satisfaction, family support, satisfaction with the family relationship and the ease of communicating with mother and father. The results indicate that the adolescents living in the shared custody system report having a better relationship with the family and reported being able to communicate with the father more easily. Considering that the number of divorces has increased, there are still very few young people who report living in the shared custody system, where there is greater contact with both parents, most of whom report that they live with one of the parents and rarely or never sees the other parent. More studies on this topic should be developed to understand which parental custody, after separation, has a better impact on the life of adolescents in a situation that in itself can create stress in adolescents